Hubungan Etos Kerja Dengan Kinerja Perawat di RUD Ngimbang - Muhammad Iqbal Ramadhan Aji; Suratmi Suratmi; Nurul Hikmatul Qowi (KOLONI, 2026)
Nursing performance is susceptible to decline due to factors such as low discipline, lack of responsibility, and insufficient commitment to professional duties. A strong work ethic is a critical factor influencing the enhancement of nursing performance, thereby ensuring the delivery of optimal nursing care. This study aimed to analyze the relationship between work ethic and the performance of nurses at RSUD Ngimbang. A quantitative study was conducted with a population of 128 nurses; a sample of 93 nurses was selected using quota sampling. Data were collected using questionnaires on work ethic and Six-Dimension Scale of Nursing Performance (SDSP)questionnaires. Following tabulation, data were analyzed using the Spearman Rank correlation test via SPSS 16.0. The results indicated that the majority of nurses possessed a “high” work ethic (58.1%), while a significant proportion demonstrated “moderate” performance (50.5%). Statistical analysis revealed a strong and significant correlation between work ethic and nursing performance ( ; ). This indicates that higher levels of work ethic among nurses are associated with better performance at RSUD Ngimbang. To improve nursing performance, it is essential to maintain and cultivate a strong work ethic through the reinforcement of responsibility, discipline, professional commitment, and continuous competency development, ultimately contributing to the improvement of nursing service quality.